Combined Spinal Epidural Anaesthesia with BiPAP-Three Case Reports - Jadon, Ashok (Medknow Publications, 2009)
SUMMARY: We report three cases where BiPAP (bi-level positive airway pressure) was used with CSEA (combined spinal epidural anaesthesia) to over come the hypoventilation due to preoperative poor respiratory reserves and additive effect of sedation. Combination of BiPAP with spinal, epidural and CSEA have been used successfully in patients of severe COPD (chronic obstructive pulmonary disease) for various surgical procedures. This combination provides safe alternative to conventional general anaesthesia, as it avoids need for postoperative ventilatory support and its deleterious effects.